2022
DOI: 10.1136/bmjopen-2022-062987
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic and changes in children’s physical activity in a rural US community: a mixed methods study

Abstract: ObjectivesTo examine differences in rural community children’s moderate-to-vigorous physical activity (MVPA) and participation in out-of-school activities from fall 2019 to fall 2020 and explore enacted PA opportunity modifications post initial COVID-19 disruption.DesignMixed methods study using the validated Youth Activity Profile (YAP), administrator reports and stakeholder surveys and semistructured interviews.SettingChildren and community stakeholders from one rural US Great Plains community in the state o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Studies conducted during the acute phase of the pandemic reported a general picture of physical activity levels reducing among adults and children [11][12][13][14], while sedentary time and screen-viewing increased [11,15]. Levels of activity were influenced by personal, organisational, environmental and policy factors [16], with less impact in rural settings which offered opportunities for outdoor play [17,18]. As lockdowns and restrictions are lifted and countries return to "normal" it is unclear how active children and adults are.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted during the acute phase of the pandemic reported a general picture of physical activity levels reducing among adults and children [11][12][13][14], while sedentary time and screen-viewing increased [11,15]. Levels of activity were influenced by personal, organisational, environmental and policy factors [16], with less impact in rural settings which offered opportunities for outdoor play [17,18]. As lockdowns and restrictions are lifted and countries return to "normal" it is unclear how active children and adults are.…”
Section: Introductionmentioning
confidence: 99%